Pemetaan Tren Penelitian Struktur Baja Sistem Portal pada Bangunan Gudang: Studi Bibliometrik Tahun 2022–2026 - Muhammad Irsal Ar Ridho Barus; Ramadhan Pratama Lubis; Muhammad Zhafransyah Lubis (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze research trends related to steel portal frame structures in warehouse buildings using a bibliometric approach based on the Scopus database during the 2022–2026 period. The research data were obtained through a search process of English-language scientific articles in the Engineering subject area, resulting in 70 relevant documents. The analysis was conducted using VOSviewer and Bibliometrix in RStudio to identify publication trends, collaboration networks, dominant keywords, and thematic developments. The results indicate that research on steel portal frame structures has shown significant growth, with major focuses on structural analysis, steel construction, and structural frames. In recent years, research has increasingly shifted toward finite element methods, numerical simulations, and structural optimization based on modern computational technology. China was identified as the country with the highest publication contribution, while the journal Structures became the most dominant publication source. This study is expected to provide references and insights for future research development in modern steel structure engineering.